2011
DOI: 10.1007/s00246-011-0038-1
|View full text |Cite
|
Sign up to set email alerts
|

Tako-Tsubo Syndrome in a 12-Year-Old Girl: Exhausted Heart, Not Broken Heart

Abstract: We report the case of a 12-year-old girl with Tako-tsubo cardiomyopathy. She was successfully treated in our Pediatric Intensive Care Unit for acute left ventricular failure, which occurred after a brief submersion in sea water. At 2-month follow-up she showed an almost complete recovery of cardiac function. We consider Tako-tsubo syndrome, which is rarely reported in the pediatric population, to be the most likely diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 10 publications
0
9
0
1
Order By: Relevance
“…Post event echocardiography in military cases is usually normal (156,196,224,352). In nonmilitary cases identifiable predisposing factors have been found, including left ventricular dysfunction (20,89) and acute coronary syndrome (137). A review of published cases and series revealed potential risk factors in approximately 50% of civilian cases (245).…”
Section: Immersion Pulmonary Edemamentioning
confidence: 99%
“…Post event echocardiography in military cases is usually normal (156,196,224,352). In nonmilitary cases identifiable predisposing factors have been found, including left ventricular dysfunction (20,89) and acute coronary syndrome (137). A review of published cases and series revealed potential risk factors in approximately 50% of civilian cases (245).…”
Section: Immersion Pulmonary Edemamentioning
confidence: 99%
“…(These latter diagnoses were not included in Table 1.) Of the 50 IPE cases found to have evidence of cardiac dysfunction, valvular disease was found in 6 cases (6,29,34) and LV dysfunction was found in 26 cases (5,11,14,20,27,35,60) ( Table 2). The mean age of those with risk factors for coronary artery disease (hypertension, hypercholesterolemia, or smoking history) was 53.0 T 6.8 yr versus 45.7 T 12.0 yr in those without risk factors (P = 0.0001).…”
Section: Resultsmentioning
confidence: 99%
“…An effort was made not to double-count cases that were likely to have been included in more than one case report or series (25,45,68). One additional article was also included, in which the case described a syndrome consistent with IPE but was not labeled as IPE or swimming-induced pulmonary edema (20). Articles related to breath-hold (apnea) diving were excluded owing to the distinct mechanism for pulmonary edema in apnea diving that does not occur during scuba diving or surface swimming (lung squeeze) (38).…”
Section: Methodsmentioning
confidence: 99%
“…1,3 Peak effects of immune modulation may take days to weeks, and given the severity of this disease process, some suggest that treatment begin prior to meeting all confirmatory diagnostic criteria. 8 The chest symptoms and electrocardiographic changes mimic those of acute myocardial infarction, but occur in the absence of coronary artery disease. 4 For patients with primary HLH and those with secondary HLH who fail to respond to first-line immunosuppressive therapy, hematopoietic stem cell transplantation is the goal.…”
Section: Discussionmentioning
confidence: 99%